Readiness of Preservice Teacher Students to Integrate Local Wisdom into Mathematics Instruction - Nurhudayah Manjani (PT. Global Research Collaboration, 2024)
This study explores the readiness of preservice teacher students to integrate local wisdom into mathematics instruction. With the growing emphasis on culturally relevant pedagogy, this research seeks to understand how PGSD students at Universitas Negeri Medan perceive the role of local wisdom in teaching mathematics. The study specifically examines students’ awareness of local cultural practices, their perceptions of the relevance of integrating these practices into math instruction, and their self-assessed confidence in applying such knowledge. A stratified random sampling technique was employed to select second- and third-year students enrolled in mathematics education courses. Data was collected through a structured Likert-scale questionnaire. The findings reveal that while students generally show high awareness and positive perceptions of local wisdom, some aspects, particularly those related to its practical application in mathematics, still require further development. Furthermore, students’ confidence in integrating local wisdom into their teaching practice varied, with some expressing uncertainty. The study concludes that although preservice teachers acknowledge the value of local wisdom, their readiness to implement it in the classroom requires more targeted training and exposure.